How does digital connection shape cultural adaptation? The impact of social media use on cross-cultural adaptation of international students in China - Xin, Yang; Shusheng, Deng; Weina, Hu; Yan, Deng (Journal of International Students, 2025)
This study proposes and validates a sequential Digital-Physical-Psychological (DPP) pathway model to explain how social media use facilitates international students’ cross-cultural adaptation through behavioral and psychological mediation. Building on Media System Dependency Theory and Social Learning Theory, the model posits that digital engagement (e.g., WeChat interactions) initiates a cascading process: it first reduces barriers to extracurricular activity participation, which subsequently enhances multidimensional social integration sense (psychological identification, social interaction, cultural adaptation). Data from 713 international students in Chinese universities, analyzed via structural equation modeling, confirmed significant direct (β = 0.27, p < 0.001) and chain-mediated effects (β = 0.04, p < 0.001), demonstrating that adaptation progresses sequentially from digital to physical to psychological domains. The findings challenge parallel-process frameworks like Ward’s ABC model, emphasizing instead the temporal dynamics of digital-era acculturation. By integrating digital pathways into adaptation theory, this study advances a structured framework for understanding technology-mediated intercultural transitions.